Fungsi Pengajian Ahad Pagi Dalam Membentuk Karakter Religius Siswa Kelas VIII Di SMP Muhammadiyah 4 Sambi Boyolali Tahun Pelajaran 2015/2016 - , Murnititah, Drs. M.Yusron, M.Ag (2016)
Education is a means to grow the characters, especially the religious character of each individual. Religious character is one character that needs to be developed in students to cultivate a behavior in accordance with the teachings of Islam which is based on the Qur'an and Hadith. Many students acted in accordance with the values of Islam are applicable both in school and in the community. Therefore, the religious character needs to be implemented and realized by the institution. One of them in extracurricular activities recitation, because the Ahad morning recitation instill character values (personality) for students, especially in the fields of religion and Kemuhammadiyahan. In this study, the problem is how Ahad morning recitation do function in shaping the religious character of eighth grade students at SMP Muhammadiyah 4 Sambi, Boyolali. Based on this background, this study aims to describe the function of Ahad morning recitals in shaping the religious character of eighth grade students at SMP Muhammadiyah Boyolali Sambi. The benefits of this research are as hasanah science, especially concerning Ahad morning recitation function in shaping the religious character of eighth grade students at SMP Muhammadiyah 4 Sambi, Boyolali. This research is a field research (field research), whereas the type of approach used in this study is qualitative descriptive. Where the research is taking place in SMP Muhammadiyah 4 Sambi, Boyolali, and the subjects in the study are responsible for extracurricular lectures, religious teachers, and students of class VIII. Source data used are primary and secondary data sources. Data collection methods used are interviews, documentation, observation. While the method of data analysis used is descriptive qualitative inductive analysis. Based on the results of research and data analysis we can conclude that (1) the recitation as a place of Islamic teachings widely, students can add new knowledge about Islam and religious insights more broadly; (2) study as a center for the development of skills (skills) pilgrims, students can hone their skills such as reading and writing the Qur'an properly, correctly and smoothly according recitation; (3) study as a community empowerment through economic and social development, students can practice and are used to save money and charity towards others; (4) study as a spiritual gathering place and recreation, besides getting new science and religious tourism, students can also socialize with the local community and can establish friendship of fellow worshipers; (5) recitation as media coaching, students feel more diligent and spirit in religious practices, eg more often carry noon prayers in congregation, Duha prayer, tadarus Qur'an after salat.